2019
DOI: 10.21037/tcr.2019.01.01
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with de novo metastatic disease in invasive breast cancer: comparison of artificial neural network and logistic regression models

Abstract: Background De novo metastasis of breast cancer is a complex clinical issue to be identified. This study was the first to construct artificial neural networks (ANN) and logistic regression (LR) models with comparison to find out important factors associated with occurrence of de novo metastasis in invasive breast cancer. Methods A total of 40,899 patients diagnosed with de novo metastatic breast cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…These in silico methods were developed using diverse features. Some methods incorporated clinicopathological-based features [20] , [21] , [22] , other methods incorporated image-based features [23] , [24] , [25] or text-based features [26] , while the more recent methods incorporate omics-based data as features. This review summarizes the in silico metastasis-related prediction methods that incorporate omics data as features.…”
Section: Metastasismentioning
confidence: 99%
“…These in silico methods were developed using diverse features. Some methods incorporated clinicopathological-based features [20] , [21] , [22] , other methods incorporated image-based features [23] , [24] , [25] or text-based features [26] , while the more recent methods incorporate omics-based data as features. This review summarizes the in silico metastasis-related prediction methods that incorporate omics data as features.…”
Section: Metastasismentioning
confidence: 99%
“…It made our research topic more consistent. With the additional information available in the clinical practice, some prediction models can predict the possibility of metastasis based on the patient's gender, age and history to assist diagnosis [32] , [33] , [34] , [35] , [36] .…”
Section: Discussionmentioning
confidence: 99%
“…Chunyan Qiu et al constructed artificial neural network (ANN) and logistic regression (LR) models in 2019 and compared them to find out the important factors related to the occurrence of new metastasis of invasive breast cancer. Finally, it is found that the artificial neural network model is superior to the traditional LR model in the recognition of breast cancer neonatal metastasis [17].…”
Section: B Development Of Deep Learning Algorithmsmentioning
confidence: 99%